Jeremiah A Commentary based on Ieremias in Codex Vaticanus. - Walser, Georg A. (Leiden : BRILL, 2012)
This is the first major commentary focusing on the Greek text of Jeremiah as it was perceived by its readers. Besides a section by section commentary, it includes a transcription, and an English translation of the text of Codex Vaticanus.
Acknowledgements; Abbreviations; Introduction; Text and Translation; Commentary; Bibliography; Index of Ancient Sources; Index of Modern Authors
Description based upon print version of record.
Keywords: Bible. O.T. Jeremiah -- Commentaries; Bible. O.T. Jeremiah I-LII -- Commentaries; Bible. O.T. Jeremiah; Bible. -- Versions -- Biblioteca apostolica vaticana; RELIGION / Biblical Studies / Prophets; Electronic books